Integrating Local Wisdom in Character Education: A Collaborative Model for Teachers, Parents, and Communities - Yusuf, Ramli; Arifin, Asriyani M; Octaviana, Uun; Abbas, Sukardi; Syawal, Julkarnain; Nurbaya, Nurbaya (AL-ISHLAH: Jurnal Pendidikan, 2024)
The implementation of character education is currently faced with various challenges, including the lack of collaboration between formal education institutions (schools), non-formal education (community), and informal education (family). Character education implemented in schools is still theoretical and textual and does not touch the context of daily life based on the local wisdom values of the local community. This research investigates local wisdom-based character education management in the ternate context through a teacher, parent, and community collaboration model. The research method used is qualitative with a case study approach. Data collection was carried out through focus group discussions (FGD), in-depth interviews, and observations to explore stakeholder perspectives on character education. This research data was analyzed descriptively through reduction, presentation, and drawing conclusions. The findings of this research reveal the success of character education management through three main programs at Madrasah Ibtidaiyah, namely the sigaro malaha (doing good) community formation program, which brings together elements of the school, family, and community. The dodoto se biasa program (teaching and habituation) for students, and the maku gawene pekan program (Embracing Each Other) in order to strengthen family attitudes and instill social character in children. These results have an impact on the holistic development of children's characters such as tolerance, collaboration (cooperation), responsibility, empathy, and love of the environment